Application of multi-criteria decision making to sustainable deep-sea mining vertical transport plans - Ma, Wenbin; Du, Yanlian; Zhang, Kairui; Shen, Yijun (Frontiers in Marine Science, 2022)
Ever since the concept of deep-sea mining was first described, the prospect of deep-sea mining testing and monitoring has proved to be a subject of great interest. Despite the considerable research and commercial attention given to developing deep-sea mining strategies, no previous study has looked explicitly at the sustainability of deep-sea mining transport plans. The objective of this paper, therefore, is to evaluate the sustainability of deep-sea mining vertical transport plans, using the methodology of fuzzy analytic network process. Major criteria for evaluating deep-sea mining vertical transport plans can be divided into technological, economic, environmental, and social components, each containing both qualitative and quantitative attributes. Weights for each criterion are determined through a questionnaire survey, completed by experts in the fields of environmental impact, policy making, marine mining, project sustainability consultancy and project economic profitability research. The research presented in this paper could be used directly in the sustainability assessment of upcoming deep-sea mining projects, furtherly contributing to the industrialization of the entire deep-sea mining industry.